ORAL SYNDROME IN SOME NUTRITION DISORDERS, DIABETES-ERGONOMICAL APPROACHES - Cristina Iordache; Ana Maria Fătu; Codrina Ancuța; Vascu Bogdan; Magda Ecaterina Antohe (Romanian Society of Oral Rehabilitation, 2020)
The term "diabetes mellitus" includes a varied number of chronic diseases characterized by hyperglycemia and relative or absolute insulin deficiency. Hyperglycemia is the most obvious biochemical marker in the complex of metabolic changes that affect carbohydrate, lipid, protid and electrolyte metabolism and can alter many organs and functions of the whole organism.The diagnosis of diabetes is based on clinical signs and laboratory explorations. The clinical picture is typical in about half of the cases and the main signs are polyuria, polydpsia, weight loss. In addition to these, others may be present in the clinical picture: asthenia, fatigue, decreased physical and intellectual strength, polyphagia. Sometimes, the diagnosis of diabetes can be revealed by the presence of signs of infectious complications, of the symptoms and signs of acute metabolic complications of diabetes or of the symptoms and signs of chronic degenerative complications. The terms of insulin-dependent and non-insulin-dependent have been eliminated, in favor of type 1 diabetes and type 2 diabetes. Type 1 is caused by autoimmune destruction of pancreatic beta cells, resulting in absolute insulin deficiency. Type 1 includes idiopathic and immune-mediated forms of β-pancreatic cell dysfunction that result in total insulin deficiency. Diabetes LADA (latent autoimmune diabetes in adults) is a recently recognized category of diabetes mellitus, which falls within the complex of type 1 diabetes. The study group consisted of 96 patients, 38 women (39.58%). and 58 men (60.42%) with oral manifestations in patients with diabetes and obesity.